Analisis Dampak Implementasi Teknologi Fintech Dalam Layanan Perbankan Terhadap Pengalaman Nasabah - Dewi Fitriana; Anggun Okta Fitri (Inflasi : Jurnal Ekonomi, Manajemen dan Perbankan, 2025)
The development of financial technology (fintech) has significantly transformed the landscape of banking services in Indonesia, reshaping how customers interact with banks. This study aims to analyze the impact of fintech implementation on customer experience, focusing on aspects such as convenience, security, ease of use, and the evolving relationship between customers and banks. A qualitative case study approach was employed, involving in-depth interviews with customers from diverse backgrounds. The findings indicate that most customers experience increased convenience and accessibility through fintech services. However, digital literacy emerges as a crucial factor influencing user experience. Data security and trust are also major concerns, with customers expecting greater transparency and education from banks regarding personal data protection. While fintech enhances efficiency, there remains a need for personal interaction, particularly among elderly customers. This study recommends that banks not only pursue digital innovation but also prioritize digital inclusion and responsive customer service across all user segments. These findings are expected to serve as a reference for the development of more inclusive and customer-centered fintech services.